Green tea extract EGCG plays a dual role in Aβ42 protofibril disruption and membrane protection: A molecular dynamic study. (January 2021) - Dong, Xuewei; Tang, Yiming; Zhan, Chendi; Wei, Guanghong
Highlights: EGCG disrupts Aβ42 protofibril in membrane environment by destabilizing two hydrophobic core regions and K28-A42 salt bridges. EGCG slows down the adsorption dynamics of Aβ42 protofibril onto lipid bilayers and alters the membrane-binding region of Aβ42 . EGCG protects lipid bilayers by reducing the membrane thinning induced by Aβ42 protofibril. Abstract: Amyloid plaques accumulated by the amyloid-β (Aβ) fibrillar aggregates are the major pathological hallmark of the Alzheimer's disease (AD). Inhibiting aggregation and disassembling preformed fibrils of Aβ by natural small molecules have developed into a promising therapeutic strategy for AD. Previous experiments reported that the green tea extract epigallocatechin-3-gallate (EGCG) can disrupt Aβ fibril and reduce Aβ cytotoxicity. The inhibitory ability of EGCG can also be affected by cellular membranes. Thus, it is essential to consider the membrane influences in the investigation of protofibril-disruptive capability of EGCG. Here, we performed multiple all-atom molecular dynamic simulations to investigate the effect of EGCG on the Aβ42 protofibril in the presence of a mixed POPC/POPG (7:3) lipid bilayer and the underlying molecular mechanisms of action. Our simulations show that in the presence of membrane bilayers, EGCG has a preference to bind to the membrane, and this binding alters the binding modes between Aβ42 protofibril and the lipid bilayer, leading to a reduced membrane thinning, indicative of a protective effect of EGCG on the membrane. And EGCG still displays a disruptive effect on Aβ42 protofibril, albeit with a lesser extent of disruption than that in the membrane-free environment. EGCG destabilizes the two hydrophobic core regions (L17-F19-I31 and F4-L34-V36), and disrupts the intrachain K28-A42 salt bridges. Our results reveal that in the presence of lipid bilayers, EGCG plays a dual role in Aβ42 protofibril disruption and membrane protection, suggesting that EGCG could be a potential effective drug candidate for the treatment of AD.